Analisis Kebijakan Pemerintah dalam Menetapkan Ibukota Kabupaten Kerinci di Bukit Tengah : MARIO DIRGANTARA, S.Sos., M.Si., M.A.P - Mario Dirgantara (JURNAL ADMINISTRASI NUSANTARA, 2019)
The establishment of autonomous regions is one of the government efforts to bring public service closer to people. Every new autonomous regions are expected to create synergy with their parent regions. The proliferation of new administrative areas also requires the establishment of new capitals which will become the icon of the area. This is where all public services and trade activities will be centralized. After the decision to proliferate the Kerinci Regency being made, the new capital of Kerinci has been moved to Bukit Tengah, Siulak. Using the qualitative descriptive method, this research presents the indicators that become the point of reference of Kerinci Regency's government in deciding the location of the new administrative capital. Keywords: public policy, public service